Wysokość obciążeń podatkowych a przerzucalność podatków - Sokołowski, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The relation between tax incidence and the level of taxation is relatively rare subject in the economic literature. The author presents the level of taxation and its trends in different countries. Then the possibilities for tax incidence of direct and indirect taxes on consumers or other producers are analyzed. In the last part of the article, the different possibilities of tax incidence and how they influence the level of taxation - especially with respect to enterprises - are researched. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 622-627